2002
DOI: 10.1002/jbm.10089
|View full text |Cite
|
Sign up to set email alerts
|

A composite graft material containing bone particles and collagen in osteoinduction in mouse

Abstract: Demineralized allogenic bone matrices (DABM) and demineralized freeze-dried bone allograft (DFDBA) have been successfully used as bone-graft materials in the treatment of acquired and congenital cranio-maxillofacial defects and in some orthopedic surgery. However, these bone-graft "powders" have many shortcomings. For example, placement of particulate graft material in a hemorrhaging site can result in inadequacies or inaccurate attachment as well as loss of the graft materials. To minimize the inadequacies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…1E, 1F). In contrast, intramuscular implantation of absorbable collagen sponge alone is known to have no bone forming effects [29]. Collectively, these studies showed that hPSCs (like their individual pericyte and adventitial components) undergo osteogenic differentiation in vitro and in vivo and thus may be useful as a purified cell source for bone formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1E, 1F). In contrast, intramuscular implantation of absorbable collagen sponge alone is known to have no bone forming effects [29]. Collectively, these studies showed that hPSCs (like their individual pericyte and adventitial components) undergo osteogenic differentiation in vitro and in vivo and thus may be useful as a purified cell source for bone formation.…”
Section: Resultsmentioning
confidence: 99%
“…1). This carrier was chosen as a nonosteoinductive carrier, as intramuscular implantation of absorbable collagen sponge alone is known to have no bone forming effects [29]. Second, an ovine DBX Putty was used (100 μl; Musculoskeletal Transplant Foundation, Edison, NJ, http://www.mtf.org).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the means to produce ECM powder and expand the potential clinical applications of this material may be important for the field of tissue engineering. The concept of using ECM powder with bioinductive properties has been utilized extensively for the delivery of demineralized bone matrix in periodontal and orthopaedic applications [17][18][19]. A powdered form of ECM provides a great deal more flexibility in terms of delivery of the material to target sites.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Moreover, the resorption rate of this biomaterial can be controlled by modifying the mixing ratios of HA and β-TCP without altering its osteoconductive properties, 6,7 and the collagen matrix should stabilize the bone particles and help with the adsorption of blood coagulum at the initial stage of healing. 8 A recent study found that CBCP composite blocks loaded with BMP-2 facilitate 3D bone regeneration in a vertical augmentation model, yielding bone with a mature appearance. 9 In terms of the release kinetics of BMP-2, ACS exhibited an initial burst release pattern of BMP-2, whereas allografts and ceramics inefficiently released BMP-2.…”
Section: Introductionmentioning
confidence: 99%